2005
DOI: 10.1002/pssa.200460417
|View full text |Cite
|
Sign up to set email alerts
|

Some benefits of Fe doped less dislocated GaN templates for AlGaN/GaN HEMTs grown by MOVPE

Abstract: Strategies for maintaining a low threading dislocation density in highly resistive GaN layers grown by MOVPE on sapphire or SiC substrates using Fe modulation doping are presented. Sheet resistances as high as 108 Ω□ for dislocation densities lower than 8 × 108 cm–2 have been obtained. 2DEGs created at the AlGaN/GaN:Fe interface have good confinement while the low dislocation density benefits the mobility: room temperature values up to 2170 cm2 V–1 s–1 have been obtained for a carrier density of 9.3 × 1012 cm–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 10 publications
(7 reference statements)
1
50
1
Order By: Relevance
“…Surface roughening was also reported by Heikman et al for their highest doping level [13]. Indeed, Bougrioua et al have demonstrated a novel method for dislocation reduction by intentionally promoting 3D growth by introducing a short period of high Fe doping, followed by a slow coalescence recovery to a 2D growth mode [11]. …”
Section: Surface Roughnessmentioning
confidence: 87%
“…Surface roughening was also reported by Heikman et al for their highest doping level [13]. Indeed, Bougrioua et al have demonstrated a novel method for dislocation reduction by intentionally promoting 3D growth by introducing a short period of high Fe doping, followed by a slow coalescence recovery to a 2D growth mode [11]. …”
Section: Surface Roughnessmentioning
confidence: 87%
“…SI templates (noted GaN:Fe-MD) were grown following procedure presented in Refs. [2,6]. Aluminium content used for AlGaN supply layers was in the range 18-26%.…”
Section: Methodsmentioning
confidence: 99%
“…High TD densities increase the leakage currents in blue and green LEDs, [6] decrease the lifetime of laser diodes, [7] reduce the efficiency of near-UV LEDs [8] and lower electron mobilities in HEMTs. [9] TDs might also be at least partly responsible for the reduced internal quantum efficiency which is typical of greenand yellow-emitting InGaN-based LEDs (the 'green gap'). Furthermore, TDs are known to cause premature junction breakdown and may prevent high gains and low dark currents from being reached in GaN-based UV avalanche photodiodes; [10,11] they can also cause current collapse in GaN-based field-effect transistors used in RF applications [12] and are generally detrimental to the performance of high-power GaN-based devices.…”
Section: à2mentioning
confidence: 99%